Ethical consulting and emerging technologies for health: a necessary dialogue - Consolandi, Monica (Medicina e Morale, 2024)
The rapid evolution of new technologies, particularly those in the health sector, requires ethical reflection that precedes their implementation rather than following it. This reflection must be integrated from the earliest stages of technological development to ensure that innovations align with fundamental ethical values and principles. In this context, a multidisciplinary dialogue is proposed that transcends the traditional separation between hard sciences and soft sciences (such as the humanities and social sciences). This integrated approach, known as “ethics by design”, aims to embed ethical considerations into the very fabric of technological design. The rapid advancement of medical technologies, such as artificial intelligence applied to diagnosis and treatment, raises new ethical issues but also ancient ones, such as privacy, patient autonomy, and equity in access to care. An ongoing and collaborative dialogue between sciences allows these challenges to be addressed holistically, keeping the human beings at the core of care. Such dialogue can contribute to a more comprehensive understanding of the ethical implications of emerging technologies, enabling the anticipation of problems and the development of solutions that respect human dignity and promote the common good. The merging of diverse perspectives facilitates a design ethics that not only meets current needs but is also capable of adapting to and addressing future changes in a responsible and sustainable manner.